El desarrollo de un subdesarrollo desigual e insustentable. Visibilizando el intercambio ecológicamente desigual que enfrentó Argentina entre 1961-2013 (Desarrollo, Estado y Espacio, 2024)
In neoclassical theory, international trade is presented as a situation that is always beneficial for both parties and as an engine of development. Starting from the theory of ecologically unequal exchange, a bridge is built between the Political Economy and the Ecological Economics that allows to demolish this postulate. The present work is based on the study of ecological footprint and verifies that Argentina has faced an ecologically unequal exchange throughout 1961-2013. However, it is also shown that this situation is not linear, but that there were deepening processes as relief processes. Finally, it is possible to show that these opposing tendencies had a lot to do with internal historical-political processes. In particular, profound changes are found in the levels of ecologically unequal exchange for the three large accumulation patterns that operated in the period.